2012
DOI: 10.1007/s12328-012-0349-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hemoperitoneum due to rupture of the paraumbilical vein successfully treated with balloon-occluded retrograde transvenous obliteration

Abstract: Spontaneous hemoperitoneum is an uncommon condition, which may be critical even if treated appropriately. The paraumbilical vein is a portosystemic collateral vein that develops in patients with portal hypertension, and is rarely found to be a source of bleeding. Here we present a case report of spontaneous hemoperitoneum due to rupture of the paraumbilical vein successfully treated with balloon-occluded retrograde transvenous obliteration (B-RTO). A 69-year-old man with cirrhosis due to nonalcoholic steatohep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Spontaneous hemoperitoneum is defined as blood within the peritoneal cavity in the absence of a traumatic cause [ 1 ]. It is an uncommon condition, and fatal if treated inappropriately [ 2 ]. It is mostly caused by bleeding from tumors, gynecological causes and rupture of an intra-abdominal blood vessel in some vascular pathologies such as aneurysms and arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous hemoperitoneum is defined as blood within the peritoneal cavity in the absence of a traumatic cause [ 1 ]. It is an uncommon condition, and fatal if treated inappropriately [ 2 ]. It is mostly caused by bleeding from tumors, gynecological causes and rupture of an intra-abdominal blood vessel in some vascular pathologies such as aneurysms and arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…It can show the presence of an intra-peritoneal effusion and the absence of other causes of bleeding (splenic rupture or hemorrhage from hepatocellular carcinoma). Shanmuganathan et al reported that attenuation values of active hemorrhage and clotted blood ranged from 85 to 370 HU (mean 132 HU) and 40 to 70 HU (mean 51 HU), respectively [ 2 , 9 ]. Interpretation of these results can sometimes be difficult for the radiologist, and this should not delay therapeutic management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arai et al showed that PTO (in failed BRTO cases) was technically successful in 44% of cases (technical success was defined as thrombosis of gastric varices on CT scan performed one week later) and when combined with standard BRTO, the success rate reached 100% (60). Sporadic case reports and case series have shown that this procedure is also effective in the treatment of ectopic varices (63,64).…”
Section: Complications and Outcomesmentioning
confidence: 99%